Molecular characteristics of a potentially novel BVDV (Pestivirus bovis) genotype 1b isolate from commercial fetal bovine serum - Pan, Juanjuan; Jiang, Jianfeng; Mi, Shijiang; Chen, Xintong; Duan, Ruli; Gao, Shandian; Kuang, Ling; Tong, Panpan; Xie, Jinxin (Frontiers in Veterinary Science, 2025)
Bovine viral diarrhea virus (BVDV) is commonly detected in biological products such as tissues and serum. This study identified BVDV contamination in a commercially available fetal bovine serum (FBS) sample. To determine whether the detected virus was infectious or merely genetic material, the FBS was inoculated into Madin-Darby bovine kidney (MDBK) cells. Following six serial passages, both indirect immunofluorescence assay results and electron microscopic visualization of viral particles confirmed the presence of infectious BVDV. The isolated strain, designated BI-2023, had a complete genome length of 12,273 nucleotides. Comparative sequence analysis showed that the 5′ untranslated region (UTR) and full genome of BI-2023 shared 87.4–97.1% and 92.4–95.2% nucleotide identity, respectively, with reference strains of BVDV1 (Pestivirus bovis) genotype 1b. Phylogenetic analyses based on the 5′UTR and whole genome placed BI-2023 within the genotype 1b cluster of Pestivirus bovis. Several amino acid substitutions were identified in the E2 and Erns proteins of the BI-2023 regions involved in immune evasion and viral secretion. This suggests this strain may represent a distinct variant within the genotype 1b group. These results highlight the critical need for routine viral screening in commercial FBS preparations.